Dragon Masters. 17 : Fortress of the Stone Dragon - West, Tracey, 1965- (West, Tracey, 1965- Dragon Masters, 2020)
Not all of the wizards who were freed from Maldred's time-trap were good wizards; one of them, Astrid, is planning on working a spell that will bring to life the bones that lie scattered in the Fortress of the Stone Dragon, bones that belonged to creatures much bigger than dragons--and when his friends are turned to stone it is up to Drake to find a way to save them, including his own dragon, Worm.